STRATEGI PENANAMAN KARAKTER DISIPLIN MELALUI PROGAM SERBUK BASNA DAN PRODAQ DI ERA TRANSFORMASI KURIKULUM MERDEKA - zaenal (Sekolah Tinggi Islam Kendal, 2021)
Character education aims to make students as the nation's successors have good morals and morals, to create a just, safe and prosperous national life. Education is one of the factors that has an important role in the formation of the character of the Indonesian nation. In the era of transformation of the independent curriculum, of course there are several new policies. The research method used in this research is descriptive qualitative research. As for data collection using observation, interview, and documentation methods, the use of data analysis in this study used the Miles and Huberman models. In this analysis using several stages of one data collection two data reduction three data presentation and the final stage is drawing conclusions. The results of this study are: 1). The implementation of the merdeka curriculum at SDN Mentosari is implemented in the 2022/2023 academic year, namely in phase A for grade one and in phase B for grade four. This curriculum gives freedom to schools to explore their abilities 2). How to explore character values ​​using a personality (psychological) and collective (social) approach. Where the personality approach is used independently and alternately for each student, while the collective approach 3). Strategies in instilling character values ​​at Mentosari Elementary School through exemplary, social action, habituation and programmed (Serbuk Basna and Prodaq).